2013
DOI: 10.1371/journal.pone.0085921
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Obstetric Fistula Prevention amongst Young Women in Urban and Rural Burkina Faso: A Cross-Sectional Study

Abstract: Obstetric fistula is a sequela of complicated labour, which, if untreated, leaves women handicapped and socially excluded. In Burkina Faso, incidence of obstetric fistula is 6/10,000 cases amongst gynaecological patients, with more patients affected in rural areas. This study aims to evaluate knowledge on obstetric fistula among young women in a health district of Burkina Faso, comparing rural and urban communities. This cross-sectional study employed multi-stage sampling to include 121 women aged 18-20 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
53
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 26 publications
18
53
8
Order By: Relevance
“…If such women develop obstetric fistula during the process of childbirth, it will also become difficult for them to get treatment since they may not even be aware that it can be treated. In a study conducted in Burkina Faso among young women, 36.4% of respondents were aware of obstetric fistula [7]. Our study however showed a higher level of awareness.…”
Section: Discussioncontrasting
confidence: 72%
“…If such women develop obstetric fistula during the process of childbirth, it will also become difficult for them to get treatment since they may not even be aware that it can be treated. In a study conducted in Burkina Faso among young women, 36.4% of respondents were aware of obstetric fistula [7]. Our study however showed a higher level of awareness.…”
Section: Discussioncontrasting
confidence: 72%
“…A study in North-Eastern Nigeria showed that 96.3% of cases of obstetric fistula had no formal education [27]. Evidence supports that knowledge and awareness on fistula amongst young women who had attained post-primary education is better in term of prevention, than women who have no education or only primary education [45]. Because of some misconceptions about the cause of fistula, it is particularly important to educate women about risks associated with early marriage and early pregnancy, including fistula, as has been implemented in Ethiopia [46].…”
Section: Recommendationsmentioning
confidence: 99%
“…It puts considerable strain on the health of affected women as a result of associated fecal and/or urinary incontinence. Obstetric fistula is largely confined to low‐resource countries owing to inadequate utilization or nonavailability of maternity services . At a fistula hospital in Ethiopia, over 90% of fistula cases occurred after prolonged (duration of labor more than 1 day) or obstructed labor; the stillbirth rate was also over 90% .…”
Section: Introductionmentioning
confidence: 99%